Investigation of in situ synthesized TiB2 particles in iron-based composite coatings processed by hybrid submerged arc welding - Kaptanoglu, Mustafa; Eroglu, Mehmet (Walter de Gruyter Gmbh, 2021)
In the study for this contribution, production of in situ synthesized TiB2 particles in iron-based composite coatings using four different submerged arc welding powders (fluxes) containing increasing amounts of ferrotitanium and ferroboron with S1 welding wire, were targeted. For this purpose, coating deposition was carried out to improve the hardness and wear properties of the AISI 1020 steel surfaces using hybrid submerged arc welding. In hybrid submerged arc welding, the welding pool is protected by both welding powders and an argon gas atmosphere. To examine the composite coatings, visual, chemical, microstructural analyses and hardness and wear tests were carried out. With the use of increasing amounts of ferrotitanium and ferroboron in the welding powders, it was observed that the microstructure of the coatings changed in terms of TiB2 particle geometries such as rectangular and hexagonal; volume fractions of TiB2 particles in the coating microstructures increased; hardness values of coatings were enhanced from 34 HRC to 41 HRC; the wear resistance of the coatings improved, and worn surface images of the coatings caused by the counter body changed from continuous with deep scratches to discontinuous with fine scratches and crater cavities.
Keywords: Hybrid submerged arc welding; TiB2; iron-based composite; coating